A Study on Extraction Pipe Insulation for Solidification Prevention of Heavy Crude Oil after Extraction - Arwinder Singh, Jigiri Singh; Muhammad Izzat Nor, Ma'arof; Suresh, Akshith; Jeyagopi, Raman; Girma, Tadesse Chala (INTI International University, 2023)
Flow assurance is a major issue in offshore pipelines that transport crude oil and gas. Heavy crude oil is causing problems due to its high viscosity during the extraction process. Solidification of crude oil, which occurs below the pour point temperature, must be prevented for efficient transport of crude oil. Thus, the aim of this study was to design a production pipe with an ideal insulation material and optimal thickness such that the crude oil temperature is maintained above the pour point temperature. The benchmark for this study was an extraction pipeline with the length of 24000 m with the outlet temperature of crude oil is 20°C for a thickness of 105mm polypropylene. The 3D models of the extraction pipes were developed using Computer Aided Design (CAD) via INVENTOR software. CFD analysis is performed via ANSYS Fluent software to determine the outlet temperature and the total heat loss from the pipe. The results for the aerogel insulation material with the thickness of 7 mm for the extraction pipe indicated that an outlet temperature of 20.3°C and a total heat loss of 382 kW is obtained. These results indicated with respect to the above benchmark, a better insulation material can be chosen on the above-mentioned criteria. However, the studies have shown, the critical role of sustainability in choosing an insulation material. In order to further improve this project, environmental factors could be considered such as corrosion and further research could be carried out into sustainable viability of solutions, against wax deposition.